Review and Improvement of Learning Outcomes of Undergraduate Chemical Engineering Program: Curriculum 2024 Case Study - Tjokorde Walmiki Samadhi; Vita Wonoputri; Hary Devianto; Guntur Adisurya Ismail (ASEAN Journal of Chemical Engineering, 2025)
Institut Teknologi Bandung (ITB) has mandated several key changes in the general design framework of the Curriculum 2024. Several institution-wide mandatory courses centered around SDG & Industry 4.0 issues were implemented as a part of the 2025-2050 ITB Development Master Plan. This paper describes the review and improvement processes undertaken by the Chemical Engineering Undergraduate Program at ITB of its Program Educational Objectives (PEO) and its entire hierarchical learning outcomes. This review was undertaken in 2023-2024 both as a part of periodic outcomes assessment and evaluation (bottom-up approach), and to define the articulation of new mandatory courses and Program offering variations required by ITB (top-down approach). The current PEO resulted from the latest revision during the Curriculum 2019 development and were deemed to be still relevant for the next 5-10 years. Direct and indirect assessments of graduate learning outcomes (CPL) since 2019 indicated a satisfactory overall attainment by the graduates and their relevance to the needs of graduates’ employers. The Program-level outcomes were also deemed to be sufficiently flexible to accommodate ITB's current policies for the new curriculum. Minor revisions were undertaken on Graduate Sub-Learning Outcomes (Sub-CPL) to better align with modern computational skillset requirements of the industry.